Food Security Legal Policy in Indonesia from the Perspective of Law as Social Engineering: Implications and Future Regulations - Debby Febrian Eprilianto; Reza Ubaidah (Universitas Negeri Surabaya, 2024)
This research examines the implications of food security law policies in Indonesia through the perspective of law as social engineering as proposed by Roscoe Pound and Mochtar Kusumaatmadja. This research is a normative legal study that emphasizes a conceptual and legislative approach. The research findings emphasize underline that the implications of food security law policies in Indonesia, viewed from the perspective of law as social engineering according to Roscoe Pound and its development by Mochtar Kusumaatmadja, indicate that law functions as an instrument of social transformation that harmonizes the interests of individuals and society, strengthens national food sovereignty, and supports sustainable national development resilient to global challenges. Future The future food security policy regulations must be designed systematically and responsively to social, cultural, and environmental dynamics, with regulatory harmonization, strengthening institutional coordination, integration of information technology, and legal protection for farmers and food business actors. This comprehensive, adaptive, and participatory approach emphasizes the role of law as a means of constructive social change and supports inclusive and sustainable national food security.